Changes in personality traits among candidates for special operations forces. Issue 3 (4th May 2021) - Bech, Søren Christian; Dammeyer, Jesper; Liu, Jie
ABSTRACT: This study examines the personality traits of 32 male candidates (Age: M = 27.2, SD  = 4.2) who completed an eight-month intensive training program to become operators in the Danish Naval Special Warfare Group (also known as Frogmen). The Frogmen candidates completed the Big Five Inventory (BFI) the day before the start of (T1) and at the end (T2) of the training program. For comparison, first year students from the Danish Technical University 2013 ( N = 192) completed the BFI at enrollment of study (T1) and one year later (T2). The results showed that Frogman candidates at T1 had significantly higher levels of Conscientiousness and Agreeableness than the university students. Relative to the university students, the Frogmen showed higher scores in Extraversion and lower scores in Neuroticism at T2 compared to T1.